INTERJECTION IN ENGLISH COMIC ONLINE ENTITLED “LINKED SOUL” - NIDA ALIFIA (Faculty of Education and Teachers Training, 2020)
This study aims to describe the interjection words used in the Linked soul online comic. This study used descriptive qualitative method. The data source is the Linked soul online comic in English. The results of the study are as follows. First, based on the type of interjection used in the comic, the researchers found 20 primary interjections and 10 secondary interjections. Second, based on its meaning, interjection can be divided into four (emotive, cognitive, conative, and phatic). Third, from the four interjection words, emotive occupies the top position (17), followed by cognitive (8), conative (4) and phatic (1). The total amount of interjection content in volume 1,3 and 5 found 36 interjections. 28 among them are the primary type and the eight interjections for secondary type.